Immunomodulatory activity of glycoproteins isolated from chickpea (Cicer arietinum L.) - Shi, Zhenxing; Li, Shiyu; Wei, Zuchen; Wang, Yuanji; Zhou, Nong; Ma, Qiang; Yao, Yang (Frontiers in Nutrition, 2022)
Chickpea (Cicer arietinum L.) is a well-known legume and widely used as the traditional medicine. This study aimed to characterize the structure and evaluate the immunomodulatory activity of one glycoprotein (CAG-1) isolated from chickpea. CAG-1 was extracted by hot alkaline water and purified with DEAE Sepharose Fast Flow and Superdex-200 column chromatography. CAG-1, with molecular weight of 8106 Da, contained 57.12% of polysaccharide and 35.41% of protein. The polysaccharide part was mainly composed of two kinds of glycosidic bonds including 2,3,4,6-Me4-Glcp and 2,3,6-Me3-Glcp, and the linkage types were measured as Glcp-(1→and 4)-Glcp-(1→. The protein part was mainly connected by Asp and Glu, and small amounts of Ala, Thr, Ser, Leu, Pro, and Phe were also detected. Nuclear magnetic resonance (NMR) analysis results indicated the presence of α-D-Glcp - (1→4)-α-D-Glcp-(1→4)-α-D-Glcp-(1→. In addition, the sugar chains in the glycoprotein were not hydrolyzed in alkaline condition, suggested that the polysaccharide was N - Glycosidic bond, thus the sugar chain was linked to the protein chain by Asp. The immunological study showed that CAG-1 stimulated the production of NO, IL-6, TNF-α and MCP-1 in RAW 264.7 macrophages in a dose-dependent manner.